Análisis Fisicoquímico de Comprimidos Recubiertos de Ciprofloxacino 500 mg realizado en Laboratorios Farmacéuticos Markos S.A. - Palma Lucio, Kiara Estefani (2017)
The pre professional practice was developed in the Quality Control Department of the Laboratorios Farmaceuticos Markos SA in the physicochemical area (control in processes), in order to perform the quality of the coated tablets of ciprofloxacin 500 mg, for which the laboratory Markos own technique was used with reference to USP 39, developing the following tests: friability, disintegration, hardness and weight control in each of the stages from the granulate to the finished product Also the test of sealing was done to the blistered. It was worked with two lords of the product, to corroborate if the manufacturing process was reproducible. It is concluded that the batches analyzed comply with the established specifications